Pergerakan Pasukan Divisi 7 Desember di Wilayah Jawa Barat (1947-1950) - Muhammad Bintang Rifkialdy; Wawan Darmawan; Murdiyah Winarti (PAKIS (Publikasi Berkala Pendidikan Ilmu Sosial), 2022)
This article is entitled “The Movement of the 7 December Division Troops in the West Java Region (1947-1950)”. The main problem discussed in this article is how the movement of the 7 December Division Troops while in West Java. The purpose of this study is to examine more deeply the movement of the 7 December Division Troops in West Java during the battle with the TNI and the policies carried out by the 7 December Division while in West Java. This research used historical method which has several steps, namely Heuristic, source criticism in which there are external and internal criticisms, interpretation and historiography. To deepen the analysis of this research, this research used the approach of sociology and conflict theory. The research used literature study technique. Based on research results, the December 7th Division was a special troop formed directly by Queen Wilhelmina. These troops were asked to come to Indonesia and be stationed in the West Java region for the task of carrying out security and order. But the security and order carried out by the 7 December Division Troops in West Java constituted colonial order and security. West Java region is a strategic place because by conquering West Java, to control the capital can easily be achieved. The December 7th Division troops had their headquarters in the Batavia area. The 7 December Division troops have guardhouses in West Java, including: Buitenzorg, Batavia, Cibadak, Cianjur, Sukabumi, Tanggerang, Cibinong, Kebalen, and Tanjung Priok. In 1950, the 7 December Division was withdrawn and relieved of duties by Dutch East Indies.                                             Keywords: 7 December Division Troops, West Java Region, Security and Order, Battle of West Java